A novel prognostic scoring model for newly diagnosed FLT3-ITD-positive acute myeloid leukemia - Zhang, Yi (Am J Cancer Res, 2020)
FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) is one of the most common somatic mutations in acute myeloid leukemia (AML). However, the molecular structure characteristics and widely accepted prognostic factors for FLT3-ITD are still not well described. This study aimed to retrospectively examine 81 patients with FLT3-ITD-positive AML diagnosed and treated at the First Affiliated Hospital of Zhejiang University from December 2013 to March 2018 using the next-generation sequencing 185-gene platform. High variant allele frequency (VAF) [> 0.48, P = 0.0089 for overall survival (OS), P = 0.13 for relapse-free survival (RFS)], multiple ITDs (> 1 ITDs, P = 0.011 for OS, P = 0.033 for RFS) and longer insertion length (> 69 bp, P = 0.14 for OS, P = 0.0078 for RFS) predicted poor survival. The study further proposed an easily applicable scoring model for OS using the Least Absolute Shrinkage and Selector Operation (LASSO) Cox regression model. Also, an independent cohort of 30 patients was used for external model validation. The mode was expressed as follows: 0.659 × FLT3-ITD VAF + 0.375 × FLT3-ITD number + 0.807 × Age + 0.688 × DNMT3A + 1.939 × U2AF1 (FLT3-ITD VAF > 0.48 scored 1; FLT3-ITD number scored 1 if carried 1 ITD, 2 if carried ≥ 2 ITDs; age > 44 years scored 1, the presence of DNMT3A or U2AF1 scored 1; 0 for other conditions). It categorized patients into low-risk (L-R, score < 1, n = 20) and high-risk (H-R, score ≥ 1, n = 61) groups based on the risk score with a significant difference in survival (3-year OS, P < 0.0001; 3-year RFS, P = 0.0005). A prognostic nomogram that integrated these five factors was developed with a concordance index calculation [OS: 0.68, 95% CI (0.64-0.72)].